2023
DOI: 10.3389/fvets.2023.1249499
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma synoviae lipid-associated membrane proteins identification and expression changes when exposed to chicken cells

Duoduo Si,
Jialin Sun,
Lei Guo
et al.

Abstract: Mycoplasma synoviae is a significant cause of respiratory disease and synovitis among chickens, and has an adverse economic impact on broiler breeding efforts. The present study was designed to develop a systematic understanding of the role that M. synoviae lipid-associated membrane proteins (LAMPs) may play in the virulence of this pathogen. Bioinformatics tools were used to identify 146 predicted membrane proteins and lipoproteins in the M. synoviae proteome. Then, Triton X-114 was used to extract LAMPs that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The subcellular localization predictions indicated that M. synoviae HPs would be found in the cytoplasm, cytoplasmic membrane, or extracellular fractions. Some HPs predicted to be both cytoplasmic and extracellular proteins were found in the surface fraction in our previous proteomic study [38]. Therefore, some HPs were also located in multiple compartments and/or served moonlight functions [42].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The subcellular localization predictions indicated that M. synoviae HPs would be found in the cytoplasm, cytoplasmic membrane, or extracellular fractions. Some HPs predicted to be both cytoplasmic and extracellular proteins were found in the surface fraction in our previous proteomic study [38]. Therefore, some HPs were also located in multiple compartments and/or served moonlight functions [42].…”
Section: Discussionmentioning
confidence: 86%
“…The M. synoviae ATCC 25204 genome consists of 720 CDSs and 673 genes, among which 155 encode HPs. However, only 8.39% of all HPs (13 out of 155) have been detected in membrane-associated lipoprotein proteomic studies [38].…”
Section: Hypothetical Proteins Encoded By the M Synoviae Atcc-25204 G...mentioning
confidence: 99%